Social preferences in chickens–effects of domestication and tameness - Gjøen, Johanna; Jensen, Per (Frontiers in Animal Science, 2024)
It has been suggested that evolution of domesticated phenotypes may have evolved as a result of correlated selection responses to reduced fear, a prominent feature in early domestication. To investigate whether domestication changes in social preferences can be attributed to increased tameness, we studied two lines of Red Junglefowl, ancestors of domesticated chickens, bidirectionally selected during 12 generations for high (HF) or low (LF) fear of humans and compared the differences between these lines to those between unselected Red Junglefowl (RJF) and domesticated White Leghorn egg layers (WL). One bird at a time was observed on its own for 12 min in an arena with one adjacent pen behind netting on each side. One of the adjacent pens contained familiar birds, and the other contained unfamiliar birds. Towards the end of the observation period, a sudden stressful stimulus was displayed, and we compared the reactions of the breeds to this as well. Male RJF spent more time close to the unfamiliar birds than WL, and performed more agonistic behaviour, but this was not mirrored in the selected birds. For females, it was WL that performed the most agonistic behaviour. Both LF and WL males showed more non-agonistic social exploration than HF and RJF respectively. Male LF and WL emitted more food calls than HF and RJF respectively. We conclude that several differences between RJF and WL were mirrored in the selection lines, with LF behaving more like domesticated WL. This is in line with the hypothesis that selection for tameness may have driven domestication related changes in social behaviour against conspecifics.